Kajian Potensi Desa di Bidang Pertanian sebagai Strategi Pemasaran Hasil Pertanian Masyarakat Desa Sentolo - Pawana, Sekhar Chandra (Jurnal Atma Inovasia, 2022)
The result that was obtained is to improve the prosperity of the people at Sentolo Village in agricultural sector, the economical strategic that was created is making the social media account to sell the agricultural product from Sentolo village. Kuliah Kerja Nyata 80 using Society 5.0 method. Group 104 of Kuliah Kerja Nyata from Atma Jaya Yogyakarta University work program was produced to increase the potential of Sentolo village in improving the economy sector in agricultural area. The types of the research was based on social facts and the data was obtained directly through Statiscic of Kulon Progo Regency latest update and Google. Secondary data was collected from literature, journals, articles and also the Internet. The data that was obtained being analyzed together on Google Drive, then understood it through Whatsapp Group and Microsoft Teams Meeting. This work will be carried out increasing the strategic of agricultural resource marketing to help people at Sentolo Village selling their agricultural product.